In Vitro Inhibition of Zika Virus Replication with Amantadine and Rimantadine Hydrochlorides - Arias Arias, Jorge Luis (2021)
Zika virus (ZIKV) is a mosquito-borne ﬂavivirus in which human infection became relevant during recent outbreaks in Latin America due to its unrecognized association with fetal neurological disorders. Currently, there are no approved effective antivirals or vaccines for the treatment or prevention of ZIKV infections. Amantadine and rimantadine are approved antivirals used against susceptible inﬂuenza A virus infections that have been shown to have antiviral activity against other viruses, such as dengue virus (DENV). Here, we report the in vitro effectiveness of both amantadine and rimantadine hydrochlorides against ZIKV replication, resulting in a dose-dependent reduction in viral titers of a ZIKV clinical isolate and two different ZIKV reference strains. Additionally, we demonstrate similar in vitro antiviral activity of these drugs against DENV-1 and yellow fever virus (YFV), although at higher drug concentrations for the latter. ZIKV replication was inhibited at drug concentrations well below cytotoxic levels of both compounds, as denoted by the high selectivity indexes obtained with the tested strains. Further work is absolutely needed to determine the potential clinical use of these antivirals against ZIKV infections, but our results suggest the existence of a highly conserved mechanism across ﬂavivirus, susceptible to be blocked by modiﬁed more speciﬁc adamantane compounds.